Spongy Myelinopathy in Newborn Beef Calves Associated with Consumption of Corn Infected with Stenocarpella maydis. (October 2019) - Odriozola, E.R.; Armién, A.G.; Ibarra, J.F. Cora; Llada, I.M.; Erreguerena, I.A.; Hecker, Y.P.; Odeón, A.C.; Morrell, E.L.; Cantón, G.J.
Summary: Stillbirth and perinatal mortality with neurological signs and lesions were diagnosed in two calves following ingestion by their dams of corn infected with Stenocarpella maydis during the third trimester of gestation. Grossly, the brain and spinal cord were unremarkable. Microscopically, diffuse severe status spongiosis of the white matter was detected in the cerebral hemispheres, brainstem, spinal cord and cerebellum. To the best of our knowledge this is the first pathological description of congenital disease in calves associated with the consumption of S. maydis -infected corn; the findings resemble those reported for the naturally occurring and experimentally induced disease in lambs.